2019
DOI: 10.3748/wjg.v25.i10.1278
|View full text |Cite
|
Sign up to set email alerts
|

Non-guided self-learning program for high-proficiency optical diagnosis of diminutive and small colorectal lesions: A single-endoscopist pilot study

Abstract: BACKGROUNDThe implementation of optical diagnosis (OD) of diminutive colorectal lesions in clinical practice has been hampered by differences in performance between community and academic settings. One possible cause is the lack of a standardized learning tool. Since the factors related to better learning are not well described, strong evidence upon which a consistent learning tool could be designed is lacking. We hypothesized that a self-designed learning program may be enough to achieve competency in OD of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Mabe et al [50] indicated that the learning effect might decrease if endoscopists do not continue their learning practice, but the required frequency of training is unclear. The recently published study of Bustamante-Balén et al [92] shows that, following a non-practice period of 6 months, a drop in performance parameters occurs, and that it takes 150 lesions to get back to previous "expert" levels. Repetitive practice therefore seems crucial for maintaining competence.…”
Section: Maintaining Competence In Optical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Mabe et al [50] indicated that the learning effect might decrease if endoscopists do not continue their learning practice, but the required frequency of training is unclear. The recently published study of Bustamante-Balén et al [92] shows that, following a non-practice period of 6 months, a drop in performance parameters occurs, and that it takes 150 lesions to get back to previous "expert" levels. Repetitive practice therefore seems crucial for maintaining competence.…”
Section: Maintaining Competence In Optical Diagnosismentioning
confidence: 99%
“…In this article, the authors mention that 250 polyps are needed to achieve competence. A Spanish study demonstrated that, following a non-practice period of 6 months, a drop in performance parameters occurs, and that it takes 150 lesions to get back to previous "expert" levels [92].…”
Section: B Training/learning Steps For Optical Diagnosismentioning
confidence: 99%
“…Although a strict adherence to NICE and Kudo classifications was not required, endoscopists used them as part of the optical diagnostic process. Firstly, HPs and SSLs cannot be differentiated within the NICE 1 category [27] and the WASP classification [28] was not recorded. On the other hand, the well-recognized interobserver variability for histological differentiation between SSLs and HPs might also bias the optical diagnosis results [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%